Dafi'iyah Al-Muta'allim Wa Al-Mu'allim Fi Ta'lim Al-Lughah Al-Arabiyyah - M. Kholis Amrullah; Ahmad Tarmizi; Faishol Mahmud Adam Ibrahim (Institut Agama Islam Negeri Metro, 2022)
The teaching and learning process is in dire need of motives and encouragements from various aspects, and it is considered among the drivers behind the behavior of the learner and the teacher, as the teaching and learning process will lose its vitality in the absence of motivation, and because it plays an important role, this research seeks to touch the theories related to motivation. Which is still the focus of the interest of educators in the field of education, in addition to that, the researcher mentioned some strategies related to motivation in terms of internal and external, such as human behavior and motivation to do something, which is among the core of this research, by looking at some references related to the topic of motives. The results of the research indicate that: There is a strong link between motivation theories, whether it is internal motivation and external motivation, each of which seeks to motivate and encourage to do something, and in this aspect is motivation in language education.